Effects of the fabric substrate on performance and durability of textile-embroidered dipole antennas. Issue 15 (August 2022) - Ventura, Heura; Parés, Ferran; Fernández-García, Raul; Gil, Ignacio; Ardanuy, Monica
In this work, several fabrics with different composition and structure have been used as the substrate for the production of wearable textile-embroidered dipole antennas. The performance of the antennas has been determined by measuring their resonance frequency, return loss and bandwidth. To determine their durability as wearable fabrics, the performance has been assessed before and after subjecting the antennas to washing and abrasion cycles. The results revealed that the woven fabrics presented a good washing fastness, even in fabrics having elastic fibers or low-crimp structures. In all cases, a good performance of the antennas was maintained after 30 washing cycles. For the abrasion cycles, the substrates with higher stability (measured as the crimp ratio) presented a higher wear fastness, whereas a higher variability was observed for the substrates with lower stability.